Evaluating the expansion of African species into Europe driven by climate change. - López-Ramírez, Sandro; Márquez-Moya, Ana Luz; Real-Giménez, Raimundo; Román Muñoz, Antonio (Wiley, 2024)
Aim: Ongoing climate change is presently influencing the distribution ranges of nu-merous species, with both range expansions and latitudinal shifts being observed.In southern Europe, a biogeographical border that separates African and Europeanbiota, while at the same time acting as a migration bridge for many species, thesechanges are of particular relevance. This study aimed to analyse the responses of ninetypically African birds to climate change to provide information on the ongoing andfuture occupation of Europe by these species.Location: Western Palearctic and surrounding areas.Methods: To this end, the distributions of the species in their native ranges were mod-elled, both in the present and in future climate scenarios, using their current breedingranges and a set of topographic and climatic variables. The climatic favourability forthe nine species was then combined using fuzzy logic.Results: The results showed that southern Europe is highly favourable for our set ofAfrican birds, except for Rüppell's Vulture, and future forecasts indicated that thisfavourability would increase further north, again excluding the African Vulture.Main conclusions: If the climate continues to warm, further arrivals of individuals areto be expected, increasing the possibility that self-sustaining populations may be-come established in southern Europe. Furthermore, new African species may startto occupy this area, with the likelihood of an Africanisation of the European fauna.Considering the role played by southern Europe as a potential focal point for the colo-nisation of this continent by African species, it is important to track their northwardexpansion and future spread.
Keywords: Cambios climáticos; Aves - Distribución geográfica; Biogeografía; African birds; Africanisation; Climate change; eBird; Favourability; Fuzzy logic; Species distribution models; Western paleartic